Effect of sleep on overnight cerebrospinal fluid amyloid β kinetics. Issue 1 (24th January 2018) - Lucey, Brendan P.; Hicks, Terry J.; McLeland, Jennifer S.; Toedebusch, Cristina D.; Boyd, Jill; Elbert, Donald L.; Patterson, Bruce W.; Baty, Jack; Morris, John C.; Ovod, Vitaliy; Mawuenyega, Kwasi G.; Bateman, Randall J.
Abstract : Sleep disturbances are associated with future risk of Alzheimer disease. Disrupted sleep increases soluble amyloid β, suggesting a mechanism for sleep disturbances to increase Alzheimer disease risk. We tested this response in humans using indwelling lumbar catheters to serially sample cerebrospinal fluid while participants were sleep‐deprived, treated with sodium oxybate, or allowed to sleep normally. All participants were infused with 13 C6 ‐leucine to measure amyloid β kinetics. We found that sleep deprivation increased overnight amyloid β38, amyloid β40, and amyloid β42 levels by 25 to 30% via increased overnight amyloid β production relative to sleeping controls. These findings suggest that disrupted sleep increases Alzheimer disease risk via increased amyloid β production. Ann Neurol 2018;83:197–204